Perception and Management of Mango (Mangifera indica L.) Dieback Disease in Actopan, Veracruz, Mexico - Noa-Carrazana, Juan Carlos (2025)
Introduction. Dieback is a serious disease reported in mango-producing regions of Mexico; however, there is no information on the perception and management of this disease by mango producers. Objective. To assess the perception of mango producers in the municipality of Actopan, Veracruz, Mexico regarding dieback disease, to evaluate the management practices they implement, and to describe their socioeconomic and production characteristics. Materials and methods. The research was conducted in the municipality of Actopan, Veracruz, Mexico in the years 2021–2022. Semi-structured interviews with 45 questions were applied to mango producers. The socioeconomic characterization of the producers, plot management, recurrent diseases, and the perception and management of mango dieack were addressed. The data obtained from the surveys were analyzed using various multivariate and descriptive statistical tools. Results. The majority of the producers were men (94 %) with a wide age range, predominantly older adults and young adults. A cluster analysis identified three distinct groups of producers: small (SPM,56 %), medium (MPM,16 %), and large (LPM,28 %) mango producers, each with specific characteristics regarding cultivated area, agronomic management, and yield (M = 8,54 ± 3,75 t/ha). The mango dieback was widely recognized by all surveyed producers; the main symptoms associated with the disease: gummosis, branch rot, and trunk rot. Only 18.75 % of the producers implement some type of specific management or control of mango dieback, mainly through chemical and mineral fungicides. Conclusions. For mango producers in Actopan, Veracruz, dieback is a highly important disease in their cultivation. They carry out some basic management strategies; however, these have not been efficient, which has led to an interest in the development of new and better control tools.